Primate Mammary Gland Insulin-Like Growth Factor System: Cellular Localization and Regulation by Sex Steroids. (1st January 2001) - Zhou, Jian; Anderson, Kristin; Bievre, Marsha; Ng, Sui; Bondy, Carolyn A.
Abstract: Background: Insulin-like growth factor 1 (IGF1) plays a critical role in estrogen-induced uterine proliferation, but it is unclear whether this estromedin function occurs in other estrogen-sensitive tissues such as the mammary gland. To elucidate this possibility, we investigated the cellular localization and hormonal regulation of mRNAs for IGF1 and 2, their cognate receptors (IGF1R, IGF2R), and IGF binding proteins 2-5 (BPs 2-5) in the rhesus monkey mammary gland. Methods: Ovariectomized monkeys were treated with placebo, estradiol (E2), and E2 plus progesterone (E2/P4) for 3 days, after which mammary tissue was harvested for in situ hybridization and immunohistochemical analyses. Results: IGF1 and IGF2 mRNA levels were significantly increased and BP2 mRNA decreased by E2 and by E2/P4 treatment. IGF1R mRNA was increased by combined E2/P treatment but not by E2 alone. BP5 mRNA was decreased by E2/P4. No differences in IGF2R, BP3, and BP4 mRNA levels were detected in any treatment group. Mammary IGF1 and IGF2 mRNA levels were both positively correlated with local epithelial proliferation, assessed by immunodetection of the proliferation-specific antigen, Ki67. IGF1 and IGF1R expression were negatively correlated with local programmed cell death, as assessed by the in situ TUNEL method. In contrast, BP2 expression was negatively correlated with epithelial proliferation and positively correlated with programmed cell death. IGF2R, BP3, BP4, and BP5 levels were not significantly correlated with either proliferation or death. Conclusions: Thus, E2-induced proliferation is associated with upregulation of both IGF1 and IGF2 expression and downregulation of BP2 expression. These data suggest that the local mammary IGF system is involved in sex steroid-induced mammary epithelial cell hyperplasia.